2016
DOI: 10.3354/meps11677
|View full text |Cite
|
Sign up to set email alerts
|

Riding the tide: use of a moving tidal-stream habitat by harbour porpoises

Abstract: Tidal-stream habitats present periodically fast-flowing, turbulent conditions. Evidence suggests that these conditions benefit top predators such as harbour porpoises Phocoena phocoena, presumably allowing them to optimise exploitation of prey resources. However, clear demonstration of this relationship is complicated by the fact that strong tidal flows often occur near-simultaneously across a wide area. The Great Race of the Gulf of Corryvreckan (western Scotland, UK) is a jetting tidal system where high-ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 46 publications
2
19
0
Order By: Relevance
“…In agreement with our results, porpoises in Land's End, Cornwall, U.K. and southwest Wales, U.K., were also found to prefer strong ebbing tidal flows for foraging (Pierpoint 2008, Jones et al 2014. Benjamins et al (2016) hypothesized that peak tidal flows may disrupt the ability for fish to stabilize their position in the water, therefore creating opportunities for predators to take advantage of disoriented prey. In addition, Jones et al (2014) suggested porpoises had adopted a foraging strategy of intercepting or "ambushing" prey during ebb tide that was concentrated on coastal and benthic topography.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In agreement with our results, porpoises in Land's End, Cornwall, U.K. and southwest Wales, U.K., were also found to prefer strong ebbing tidal flows for foraging (Pierpoint 2008, Jones et al 2014. Benjamins et al (2016) hypothesized that peak tidal flows may disrupt the ability for fish to stabilize their position in the water, therefore creating opportunities for predators to take advantage of disoriented prey. In addition, Jones et al (2014) suggested porpoises had adopted a foraging strategy of intercepting or "ambushing" prey during ebb tide that was concentrated on coastal and benthic topography.…”
Section: Discussionsupporting
confidence: 90%
“…Benjamins et al . () hypothesized that peak tidal flows may disrupt the ability for fish to stabilize their position in the water, therefore creating opportunities for predators to take advantage of disoriented prey. In addition, Jones et al .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations